A relação entre responsabilidade social empresarial e desempenho financeiro em empresas do Rio Grande do Sul - Friedrich, João (2015)
Companies are subject to enormous pressure from stakeholders related to social aspects. As a result, companies were evaluated not only through traditional performance indicators, but also through the way they interact with a wide range of social demands. The issue of corporate social responsibility (CSR) is associated with a wide spectrum of relations between the company and its stakeholders, as well as for the environment. In this context, there have been several studies investigating the effective feasibility of the relationship between social responsibility and profit. The positive results of financial performance would be associated with the set of expectations of stakeholders. Thus, this study aims to answer what is the relationship between the financial result of the behavior of the largest companies in Rio Grande do Sul and its CSR activities. Therefore, the research sought to companies that are among the 100 largest in the year 2013, according to the classification by Value Weighted Greatness (VPG) of the journal Tomorrow, publicly traded traded on BM & FBOVESPA that published the BS model IBASE between 2009 and 2013. In view of these criteria resulted in three companies that were analyzed their CSR and DF indicators. As a result it was not possible to infer that there is a correlation between social, environmental and financial variables of the companies studied.